From Seed to Sale – Understanding Financial Constraints in Northern Sri Lanka’s Paddy Sector - Mithila, G. (The Association of Sri Lanka Academics in Japan, 2025)
This study examines the financial challenges faced by small paddy farmers in Killinochchi, a district in Northen Sri Lanka that is recovering from war conflict. Although these farmers play an important role in ensuring the country’s food supply, they struggle to get loans from banks, store their harvests properly and connect with better markets. The study is based on interviews with twenty farmers and uses thematic analysis to understand their experiences. Five main issues were found, which are a lack of access to formal credit, dependence on informal loans, the need to sell crops quickly after harvest, poor financial knowledge, risks from flood and droughts, and limited awareness of better market options. These problems keep farmers stuck in a cycle of debt and low profits. The study suggests that improving access to affordable credit, building better storage facilities, offering financial training and linking farmers to export markets can help strengthen their income and improve rural development.
Keywords: Climate risk; Financial exclusion; Informal credit; Post-harvest constraints; Rural finance